Synergistic improvement of thermal conductivities of polyphenylene sulfide composites filled with boron nitride hybrid fillers. (April 2017) - Gu, Junwei; Guo, Yongqiang; Yang, Xutong; Liang, Chaobo; Geng, Wangchang; Tang, Lin; Li, Nan; Zhang, Qiuyu
Abstract: Hybrid fillers of micrometer boron nitride/nanometer boron nitride ( m BN/ n BN) were employed to fabricate the highly thermally conductive insulating m BN/ n BN/polyphenylene sulfide (( m BN /n BN)/PPS) composites via mechanical ball-milling followed by hot-compression method. The thermally conductive coefficient ( λ ), dielectric constant ( ε ) & dielectric loss tangent (tan δ ) values and thermal stabilities were all enhanced with the increasing addition of m BN/ n BN hybrid fillers. The λ value was improved from 0.286 W/mK for pristine PPS matrix to 2.638 W/mK for the ( m BN /n BN)/PPS composite with 60 wt% m BN/ n BN (mass fraction, 2:1) hybrid fillers. Appropriate addition of the m BN /n BN hybrid fillers played a role of heterogeneous nucleation for PPS matrix. Agari model fitting revealed that the m BN/ n BN hybrid fillers could be much easier to form the continuous thermally conductive channels & networks. The corresponding ε and tan δ values still maintained relatively lower level of 3.96 and 0.022, respectively. And the corresponding THeat-resistance index ( THRI ) value was beyond 277.8 °C.